Stability of metallo-porphyrin networks under oxygen reduction and evolution conditions in alkaline media. Issue 5 (18th January 2019) - Hötger, Diana; Etzkorn, Markus; Morchutt, Claudius; Wurster, Benjamin; Dreiser, Jan; Stepanow, Sebastian; Grumelli, Doris; Gutzler, Rico; Kern, Klaus
Abstract : Understanding catalyst stability requires real-space insight on the molecular level and complementary spectroscopic characterisation. Abstract : Transition metal atoms stabilised by organic ligands or as oxides exhibit promising catalytic activity for the electrocatalytic reduction and evolution of oxygen. Built-up from earth-abundant elements, they offer affordable alternatives to precious-metal based catalysts for application in fuel cells and electrolysers. For the understanding of a catalyst's activity, insight into its structure on the atomic scale is of highest importance, yet commonly challenging to experimentally access. Here, the structural integrity of a bimetallic iron tetrapyridylporphyrin with co-adsorbed cobalt electrocatalyst on Au(111) is investigated using scanning tunneling microscopy and X-ray absorption spectroscopy. Topographic and spectroscopic characterization reveals structural changes of the molecular coordination network after oxygen reduction, and its decomposition and transformation into catalytically active Co/Fe (oxyhydr)oxide during oxygen evolution. The data establishes a structure–property relationship for the catalyst as a function of electrochemical potential and, in addition, highlights how the reaction direction of electrochemical interconversion between molecular oxygen and hydroxyl anions can have very different effects on the catalyst's structure.